IMPLEMENTASI LOAD BALANCING SISTEM CLUSTER SERVER PADA WEB SERVER UNTUK JAMINAN KETERSEDIAAN LAYANAN TINGGI - Fauzi, Adnan (Jurnal Sistem Komputer, 2021)
Website services have become especially important thing and are the primary need of everyone’s information needs. This High information needs require website services to be reliable so that it doesn’t disrupt it’s user. Problems often happened in the website services when the infrastructure supporting it was having system failure, such as power shortage, natural disaster, hardware failure, and internet network problem etc. To increase website services’ system reliability and optimal service, infrastructure system that support server cluster schema is needed. The objective of infrastructure system that support server cluster schema is to increase website services’ system reliability and minimize downtime. Server cluster allow website services to look undisturbed on the user’s view even though there are some problems happening in the main server such as power shortage, because the website services is being serve by backup server using failover function. Infrastructure’s requirement for implementation of cluster server system at least needs to be double from the main system used, so that when the main system had hardware or software problems the backup system can serve website services just as good as the main system. It is hoped that website services will always available and the services is undisturbed even though there are problems in the infrastructure.